Noonan Syndrome pada Bayi Perempuan 6 Bulan: Sebuah Laporan Kasus - Chindy Setia Putri; Ismi Citra Ismail; Epriyan Saputra (CV. Jasa Sukses Abadi, 2026)
Noonan syndrome (NS) is an autosomal dominant genetic disorder with significant phenotypic overlap with Turner syndrome (TS). Given these overlapping physical stigmata, accurate diagnosis requires a comprehensive multisystem clinical evaluation and molecular genetic confirmation, particularly when cytogenetic karyotyping yields normal results. A 6-month-old female infant was referred with an initial suspicion of TS, suspected hydrocephalus, and significant gross motor developmental delay. Physical examination revealed characteristic craniofacial and skeletal phenotypic stigmata mimicking TS, including webbed neck, bilateral microtia, low-set ears, hypertelorism, wide-spaced nipples, and bilateral single palmar creases. Echocardiography showed congenital heart disease consisting of mild pulmonary stenosis and a small atrial septal defect. Brain non-contrast CT scan demonstrated Benign Enlargement of the Subarachnoid Space in Infancy (BESS) with mild ventriculomegaly, ruling out obstructive hydrocephalus. Cytogenetic karyotype analysis revealed a normal 46,XX female karyotype, thereby definitively excluding classic TS (45,X). The combination of physical stigmata overlapping with TS, a normal 46,XX karyotype, and the presence of pulmonary stenosis leads to a strong clinical suspicion of Noonan syndrome (strongly suspected Noonan syndrome). However, because molecular genetic testing has not been performed, the diagnosis of NS in this patient remains a clinical diagnosis. This case highlights the importance of a holistic diagnostic approach to differentiate TS and NS phenotypes. Further molecular genetic testing, such as a Targeted Next-Generation Sequencing (NGS) panel for RASopathy genes (PTPN11, SOS1, KRAS, RAF1) or Whole Exome Sequencing (WES), is highly recommended to identify the specific causative gene mutation and achieve a definitive molecular diagnosis.